Polyalphabetic Substitution Cipher Using Multiple Random Table - Kartha, Ranju S; Paul, Varghese (International Journal of Computer Sciences and Engineering, 2025)
There are many cryptographic techniques available for providing a secure communication. Encryption technique can be classified according to their encrypting process. They are substitution cipher and transposition cipher. Polyalphabetic cipher is based on substitution technique- the plaintext letters are encrypted differently depending upon their placement in the text and the keyword. Vigenere cipher is considered to be the most efficient and simplest Polyalphabetic substitution cipher. Due to its repeating nature of the keyword, it is vulnerable to attacks. To overcome this, here we are presenting a new cipher which uses multiple random Tables (26x26) for encryption. In this proposed cipher, the keyword is repeating until it is equal to the length of the plaintext. But here, whenever the keyword repeats, this cipher generates different 26x26 random tables for encryption. Also, each table will be completely independent of the previous table. So this proposed Polyalphabetic cipher is unbreakable.